A Total Content of Phenolic Compounds in the Ethanol Extracts of Galega officinalis L. and G. orientalis Lam.: Abstract - Shymanska, Oksana; Vergun, Olena; Rakhmetov, Dzhamal; Brindza, Ján; Ivanišová, Eva (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
This study represents results of determination of total phenolic compounds in raw of two species of Galega L. It was investigated plant extracts of Galega officinalis L. (goat’s-rue) and Galega orientalis Lam. (fodder galega) which are known as fodder crops with high productivity of green mass and medicine plants (Hasani-Ranjbar et al., 2009; Peiretti, 2009; Shojaee et al., 2015; Teleută et al., 2015). The current study was aimed to evaluate an accumulation in selected plants the total content of phenolics as compounds with antioxidant activity. Raw of investigated plants collected from experimental collections of M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv) during vegetation. Biochemical analysis conducted in the Slovak University of Agriculture in Nitra. The phenolic content in ethanol extracts was measured using Folin-Chocalteu reagent. The procedure for preparing extracts was done according to Singleton and Rossi, 1965 and measuring conducted using spectrophotometer Jenway (6405 UV/Vis, England). Gallic acid was used as the standard and the results were expressed in mg g-1 gallic acid equivalent (GAE). Study of G. officinalis extracts showed that accumulation of total phenolic content in different organs was in the range from 9.13 to 32.76 mg g-1 GAE. In extracts of G. orientalis was identified total phenolics content from 6.73 to 26.77 mg g-1 GAE. It was established that less concentration of studied compounds found in the stems for both species.